2023
DOI: 10.21203/rs.3.rs-2541570/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Floristic Composition, Structure, and Regeneration Status of Woody Plant Species in Hurubu Natural Forest,North Shewa, Oromia Region, Ethiopia

Abstract: Ethiopia harbours the Eastern Afromontane and Horn of Africa hotspots of biodiversity.The general objective of this study was to investigate the floristic composition and diversity of species, the structure and the regeneration status of the Hurubu natural forest. Three parallel transects was systematically laid across the forest with an interval of 200m in north to southt direction. Thirty sample quadrats of 20 m × 20 m was placed along transects at an interval of 100 m for mature trees and shrubs, while for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Of the others, four are of least concern (LC) and two are near threatened (NT). The number of endemic species reported in the current study is somewhat lower than reported from other related forests where full inventories have been performed, e.g., 13 endemic species in Dirki and Jato forest (Tadesse, 2015) and 10 species from Sese Forest (Belachew, 2010). The differences may be the consequence of the sampling effort.…”
Section: Floristic Composition Of the Ntfps In Sera Forestcontrasting
confidence: 74%
See 1 more Smart Citation
“…Of the others, four are of least concern (LC) and two are near threatened (NT). The number of endemic species reported in the current study is somewhat lower than reported from other related forests where full inventories have been performed, e.g., 13 endemic species in Dirki and Jato forest (Tadesse, 2015) and 10 species from Sese Forest (Belachew, 2010). The differences may be the consequence of the sampling effort.…”
Section: Floristic Composition Of the Ntfps In Sera Forestcontrasting
confidence: 74%
“…We have shown that Sera Forest is rich in plant species compared to similar forests in Ethiopia. Although we have recorded species for NTFPs only, their number is higher than recorded in floristic investigations in Jibat Forest in West Shewa Zone (131 species) (Bekele, 1993); Menagesha Suba forest in West Shewa zone (135 species) (Belachew, 2010) and Komto forest in East Wollega Zone (103 species) (Gurmessa et al, 2012). Fabaceae is the most common family in our study, followed by Asteraceae.…”
Section: Floristic Composition Of the Ntfps In Sera Forestcontrasting
confidence: 63%
“…The total basal area of Pugnido Forest (82.5 m 2 ha −1 ) was much higher than the average basal area of tropical forests (35 m 2 ·ha −1 ) [ 33 ]. In addition, the basal area of the study forest was higher than some of the Ethiopian forest patches such as Nech Sar [ 2 ], Weiramba [ 19 ], Gole [ 16 ], and Yemrehane Kirstos Church [ 20 ], but it was lesser than Berbera Forest [ 32 ], Gelesha Forest [ 34 ], Boda Forest [ 35 ], and Sese Forest [ 36 ]. Many forests in different locations may have varied basal areas due to differences in the forest's age, successional stage, geographic position, or conservation status.…”
Section: Discussionmentioning
confidence: 99%
“…Importance value index (IVI) is useful to differentiate each species' ecological relevance [ 12 ] in which species' social structure in the community is high when the IVI value is high. Therefore, the leading species such as Albizia lebbeck, Kigelia aethiopum, and Combretum adenogonium might be the most adaptable and successful species that resist external and internal disturbances with good reproduction, regeneration, and recruitment as described by Belachew [ 36 ], but lower IVI values of some species might be related to their poor adaptability for the natural ecology of the area.…”
Section: Discussionmentioning
confidence: 99%